Optimization of molding parameter effect to warpage of car bumper based on plastic flow simulation software - Mohd Nasrul Mahmudi, Mahmud (2009)
This research is specially focused on finding optimum molding parameter effect to warpage of a car bumper. The objectives of this research are to study the influence of injection molding parameters on a car bumper and analysis model car bumper using plastic flow simulation software. The idea of this project came when injection molding is the most widely used process in automotive industry. Since the qualities of injection molded plastic part are mostly influenced by process condition, how to determine the optimum process conditions becomes the key to improving the part quality. The optimization of molding parameter effect is very important for the automotive industry because it gives beneficial effects in production costs due to less material being used and shorter cycle times. In this project, plastic flow simulation method is proposed to optimize the molding parameter effect to warpage of a car bumper. The car bumper will be analyzing using three different parameters such as mold temperature, melt temperature, and injection pressure. This parameter will be changed to see the effect on car bumper. The result shows that the plastic flow simulation method is an effective tool for the process optimization of injection molding.